Analisis Kualitas Hasil Pengomposan Metode Takakura Dengan Menggunakan Bioaktivator EM-4 Dan Maggot - Putri, Dhea Ayu Amalia; Puspikawati, Septa Indra (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The environment has an important role in the survival of living creatures on earth. One of the environmental problems that will always be produced every day is waste. Indonesia is one of the countries with the largest population which is predicted to increase every year. This population can increase the amount of waste generated. According to SIPSN data, the amount of waste generation in Indonesia reached 33,133,124 tons/year and in Banyuwangi Regency it was 305,313 tons/year, of which 130,160 tons/year of unmanaged waste came from organic household waste. This research aims to determine the comparison of the quality of the results of the physical parameters temperature, color, smell, pH, humidity between treatment I (EM-4) and treatment II (Maggot) in making compost using vegetable waste using the Takakura method. This research method uses a field experimental design carried out at the FIKKIA Environmental Health laboratory at Airlangga University in Banyuwangi from February to March 2024 with descriptive and comparative analysis. The results of this research for color, smell and temperature parameters between EM-4 and Maggot meet the requirements, namely blackish color, smells like earth, and temperatures of 34.6?C and 37?C. The pH parameters do not meet the standards, namely4.68 and 5.36, which means it is acidic. The moisture parameter of only the Maggot bioactivator meets the standard, namely48.6%, while EM-4 does notnamely 59%, which means that making compost using the Takakura method using the help of the Maggot bioactivator has a greater influence on the decomposition results of composting organic waste.